Phenomenological Study of Fatherlessness in the Lives of Daughters - Pratiwi, Mutia Rahmi; Yusriana, Amida; Poernomo, Moudy (JURNAL ILMU SOSIAL, 2024)
In a family, both the mother and father’s roles are equally important. A father's role goes beyond being the breadwinner or the head of the family; he is also expected to play a complete role in supporting a child's development and sharing responsibilities with the mother as a wife. When a father doesn't fulfill his role effectively, the issue of "fatherless" arises in the family, which has long-term impacts on the child, including a daughter's perception of her future life partner. Previous research has shown that the absence of a father's role at home (fatherlessness) can influence how a child interacts and shapes a child's preferences in choosing a partner or determining their romantic relationships. This study, employing phenomenology and in-depth interviews with four female informants who have experienced fatherlessness, draws on family communication, attachment theory, penetration theory, and gender role theory. The research findings highlight that the experience of fatherlessness becomes a major communication barrier, affecting the informants in initiating romantic relationships. Respondents express difficulties in trusting and maintaining open communication with close friends. They state that disappointment in their father figure leads them to seek a partner to fulfill their psychological needs related to the missing fatherly figure. The study also confirms factors influencing the perceptions of fatherless daughters in choosing life partners, including a father's involvement in child-rearing, healthy communication between father and child, traumatic experiences, and current parent-child communication relationships. This research can serve as a reference for further studies interested in examining family communication from the perspective of the father's role and the communication between daughters and their fathers.